Downsizing chronic disease management programs for type 2 diabetes patients during the COVID-19 pandemic: changes in healthcare utilization patterns - Rijpkema, Corinne; Ramerman, Lotte; Peters, Lilian; Muris, Jean; Olde Hartman, Tim; Homburg, Maarten; Bos, Isabelle; Verheij, Robert (Frontiers in medicine, 2025)
During the COVID-19 pandemic, chronic disease management programs (CDMP) for Dutch type 2 diabetes patients by general practitioners (GP) were scaled down. These programs aim to improve diabetes prognosis through appropriate interventions and avoid hospital treatment. However, it remains unknown whether downsizing CDMP increased care in other settings. Therefore, we examined the changes in healthcare utilization for type 2 diabetes patients during the COVID-19 pandemic including CDMP, GP out-of-hours care, hospital care, and regular GP care. Routine healthcare data from electronic patient records of GPs, participating in Nivel Primary Care Database, of 15,247 Dutch type 2 diabetes patients enrolled in CDMP, were linked to GP out-of-hours registration data and hospital claims data. Regression analyses compared healthcare utilization in 2020 and 2021 (pandemic) to 2019 (non-pandemic). For most quarters of 2020 and 2021, care through CDMP was significantly lower, down to 38% in Q2 of 2020 compared to 2019. In Q1 of 2020, type 2 diabetes patient visits to out-of-hours GP services rose notably, but decreased in Q1 of 2021, compared to 2019. Hospital care for diabetes showed a significant increase in Q2 of 2021 (+11.3%), compared to Q2 2019 and regular GP care increased from Q1 2021 (up to +11.1% in Q3 2021). Although no significant differences were observed in other quarters, there were different trends visible. Reduced CDMP contacts in 2020 were significantly associated with increased regular GP care in 2021. Moreover, reduced CDMP in early 2021 was significantly associated with more regular GP care and hospital care later in 2021. Downscaling CDMP care for type 2 diabetes patients during the COVID-19 pandemic was associated with temporary increases in hospital care for diabetes and regular GP care at various times during the pandemic. These findings may contribute to making informed decisions regarding measures during future pandemics, and, therefore, the pandemic provided a unique learning opportunity for the healthcare system in delivering appropriate care through CDMP. In future pandemics, it will be essential to implement adaptations such as telemedicine to mitigate health deterioration and alleviate pressure on other healthcare services.